The Centre for Continuing Education and Extension Services: A Legacy of Excellence and Access to Life-long Learning - Rahming-Nwosa, Christina; Bastian-Jones, Lorraine; Bethel, Edward Clement; Munroe, Altamease; Sherman, Denise (International Journal of Bahamian Studies, 2015)
A review of the history and evolution of the Centre for Continuing Education and Extension Services and the various programmes it has developed to support the work of the College of The Bahamas.